Effectiveness Of Coagulationflocculation Process For The Removal Of Chemical Oxygen Demand (Cod), Color And Suspended Solid In Industrial Wastewater Treatment - Damanhuri, Nur Amira Nadia (Universiti Sains Malaysia, 2018)
The presence of latex wastewater in the environment gave negatives impact on the water quality by causing many such a problems such as colour, odour and etc. Other than that, it can bring harmful effect to society and wild life population because water is one of essential part of life. Therefore, it is important to treat wastewater before releasing into the surface water. For this study, coagulation and flocculation process had been conduct to maximize the removal of COD, suspended solid and colour using aluminium and ferric chloride as coagulant. Other parameters are also included in this study such as turbidity, BOD and UV254mm for more data collection. For average sample of wastewater, coagulation using alum with pH 6 showed the highest percentage of removal of colour and suspended solid with 96.35% and 99.45% at optimum dose of 80 mg/L. However, for COD removal show little percentage a removal, which is 33.05 %. Coagulation using ferric chloride with pH 6.0 showed the highest removal of colour and suspended solid with 99.25% and 99.5% at optimum dose of 300 mg/L. However, the COD removal only 37.75%. It can be state that, coagulation / flocculation did not improve the removal of COD in wastewater. Thus, it requires more treatment. For this study, it can be conclude that the use of ferric chloride was better in removing colour and suspended solid compared to alum.